Nilai Kepemimpinan Arjuna dalam Lakon Begawan Ciptaning Serta Peran Ki Purbo Asmoro sebagai Pemimpin Budaya - Priyanto Priyanto; Hanief Hanief (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study explores the leadership values embedded in Wayang Kulit Purwa, particularly in the play Begawan Ciptaning performed by Ki Purbo Asmoro in Pécs, Hungary, in 2023. The research stems from the view that Javanese leadership is not merely oriented toward authority but emphasizes spiritual harmony, morality, and cosmic responsibility toward life. The purpose of this study is to reveal the leadership values of Arjuna as Begawan Ciptaning and to examine the role of Ki Purbo Asmoro as a cultural leader who effectively adapts Javanese leadership philosophy within a global context. The research employs a qualitative interpretive approach with two main dimensions: empirical observation of the performance and conceptual analysis using cultural semiotics. The findings indicate that Arjuna embodies a model of spiritual leadership grounded in the principles of Astha Brata and the concept of Hamemayu Hayuning Bawana, while Ki Purbo Asmoro acts as both puppeteer and cultural leader who conveys ethical values through artistic innovation and cultural diplomacy. This study concludes that Wayang Kulit Purwa functions not only as a traditional performing art but also as a living philosophy and a medium of leadership education that fosters moral, spiritual, and universal human awareness remaining highly relevant for shaping ethical leadership paradigms in the global era.